Seminar for strengthening capacities in hospital management for Peru - Ayala Peralta, Félix Dasio (2024)
The article provides a comprehensive overview of the "Seminar on Strengthening Hospital Management Capacities in Peru," held in Beijing, China, from May 30 to June 13, 2023. This event brought together a delegation of 22 Peruvian health managers who participated in 17 lectures and technical visits organized by the People's Hospital of Peking University, in collaboration with the Center for International Exchange and Cooperation of the Health Commission and the Ministry of Commerce of China. The academic program covered topics such as hospital quality and safety, infection prevention, logistics management, digital transformation, and continuing medical education. It provided innovative tools applicable to the Peruvian healthcare system while offering a key space to contextualize the current situation of Peru’s health systems concerning the quality of medical care and the need to strengthen hospital management capacities. The event stood out not only for its high academic standards but also for its impact on modernizing hospital management and promoting international collaboration, underscoring the shared commitment to sustainable development in the healthcare sector. The knowledge gained provides a starting point for implementing significant improvements in health services in Peru.